Khivan Historical Manuscripts of the 19th-the Early 20thCentury - Тулибaевa Ж. М. (Journal of Oriental Studies, 2018)
This article is based on the research some of Khiva historical works. The surviving Khivan narrative sources due to their content and diversity of facts have a special place among manuscripts of the Central Asian region. In the works of Khiva historiographers are contained comprehensive data on the history of the nomads, including Kazakhs that inhabited the territory of the Khivan khanate and its neighboring countries. The Khivan historical manuscripts contain data specifying the tribal structure of Kazakhs of the Khivan Khanate as well as their settlements.The article is written in framework of realization of project No.AP05132796 of the Ministry of Education and Science of the Republic of Kazakhstan.